Trypanosomiasis in N'Dama cattle under village management in Zaire - Ngamuna, S.; D'Ieteren, G.D.M.; Itty, P.; Leak, S.G.A.; Maehl, J.H.H.; Minengu, M.; Nagda, S.M.; Paling, R.W.; Rarieya, J.M.; Thorpe, W.R.; Trail, J.C.M. (ILCA/ILRAD, 1988)
Reports the prevalence species and intensity of trypanosome parasitaenia (1986-1987) for N'Dama cattle managed in village herds inforest and plateau areas of Idiofa, Zaire, Examines tsese challenge & its relationshipto trypanosome prevalence. Reports the duration of infection, pattern of parasitaemia and the effects of trypanosomiasis and other diseases on PCV. Gives preliminary performance data.